2010
DOI: 10.1590/s0100-29452010005000116
|View full text |Cite
|
Sign up to set email alerts
|

Rentabilidade econômica do cultivo do maracujazeiro-amarelo sob diferentes podas de formação

Abstract: O objetivo deste trabalho foi analisar a rentabilidade econômica do maracujazeiro-amarelo, sob diferentes formações da planta. O experimento foi conduzido em pomar comercial no Município de Lavras-MG (21º 14' S; 45º 58' W; 910 m de altitude), durante dois ciclos de produção (2006/2007). Os tratamentos constituíram na formação das plantas com diferente número de ramos terciários (T1=40, T2=30, T3=24, T4=20 e T5=14 por planta). O delineamento utilizado foi em blocos casualizados, com quatro repetições, sendo a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
0
9
0
7
Order By: Relevance
“…Araújo Neto et al (2008) reported that inputs along with labor were 57.83% compared to minimal cultivation and 60.46% compared to conventional tillage. Hafle et al (2011) reported that passion fruit plants training pruning account for 73.9% from inputs along with labor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Araújo Neto et al (2008) reported that inputs along with labor were 57.83% compared to minimal cultivation and 60.46% compared to conventional tillage. Hafle et al (2011) reported that passion fruit plants training pruning account for 73.9% from inputs along with labor.…”
Section: Discussionmentioning
confidence: 99%
“…Research with yellow passion fruit, in several regions of Brazil, have shown that this specie, in spite of having a high production cost and also a negative price fluctuations in the consumer market, has economic potential to increase employment and as well financial return; which has been matched and has often exceeded the rates achieved by the main crops in the country such as other species of fruit trees, cereals and vegetables crops (Kits et al, 1996;Araújo Neto et al, 2008;Arêdes et al, 2009;Hafle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O maracujá amarelo (Passiflora edulis f. flavicarpa), também conhecido como maracujá-azedo, representa aproximadamente 95% da produção nacional (Hafle et al, 2010). O Estado do Pará é o oitavo maior produtor brasileiro e no ano de 2014 produziu 20.329 t (IBGE, 2015).…”
Section: Introductionunclassified
“…O Estado do Pará é o oitavo maior produtor brasileiro e no ano de 2014 produziu 20.329 t (IBGE, 2015). No entanto, ao mesmo tempo em que surgem novas áreas de cultivo e há a expansão da cultura, observa-se o aparecimento de diversos problemas fitossanitários (Hafle et al, 2010). Dentre as doenças que ocorrem no maracujazeiro, a mancha bacteriana (Xanthomonas axonopodis pv.…”
Section: Introductionunclassified